2015
DOI: 10.1016/j.socscimed.2015.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of the relationship of functional literacy and numeracy to geographical health inequalities

Abstract: The relative contributions of functional literacy and functional numeracy to health disparities remain poorly understood in developed world contexts. We seek to unpack their distinctive contributions and to examine how these contributions are framed by place-based deprivation and rurality. We present a multilevel logistic analysis of the 2011 Skills for Life Survey (SfLS), a representative governmental survey of adults aged 16-65 in England. Outcome measures were self-assessed health status and the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
2
9
1
1
Order By: Relevance
“…The numeracy items included medication adherence, reading and comprehension of the prescription and drug label, and medication expiration awareness. Though no association between poor numeracy skills and adherence behavior was found in this study, other studies have shown poor numeracy skills to be associated with medication adherence failure and poor health [ 20 , 47 , 48 ]. Most studies conflate the concepts of health literacy and health knowledge [ 49 ].…”
Section: Discussioncontrasting
confidence: 96%
“…The numeracy items included medication adherence, reading and comprehension of the prescription and drug label, and medication expiration awareness. Though no association between poor numeracy skills and adherence behavior was found in this study, other studies have shown poor numeracy skills to be associated with medication adherence failure and poor health [ 20 , 47 , 48 ]. Most studies conflate the concepts of health literacy and health knowledge [ 49 ].…”
Section: Discussioncontrasting
confidence: 96%
“…The bivariate analysis showed that the five demographic variables of age, education level, primary language, primary caregiver identity, and willingness to receive a transplant are associated with the overall health literacy of hemodialysis patients. The association of age and overall health literacy is consistent with the existing literature, which indicates that older patients tend to have poorer health literacy [ 23 ]. Furthermore, the findings of better health literacy in more educated patients are also consistent with existing literature.…”
Section: Discussionsupporting
confidence: 88%
“…Consumers' ability to correctly understand information shown on product labels can be essential for health and safety [1] or to simply make an informed choice regarding sustainability, respective of personal principles and values [2][3][4]. Indeed, informed decision-making depends on people's ability "to accurately evaluate and understand information about risk" related to a product or a situation [5].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, a good drug label design could be based on expertise and sound human-centred design principles [12]. Three aims can be attributed to labelling of food products [13]: (1) information Is "human factor" applied to "label" design in the current scientific scenario? What are the fields in which these concepts have been most explored?…”
Section: Introductionmentioning
confidence: 99%